Eco-design in Electrical Engineering Eco-friendly Methodologies, Solutions and Example for Application to Electrical Engineering - Bessède, Jean-Luc.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book addresses eco-design, a major tool for reducing the environmental impacts of products, services and systems in the context of sustainable development. It covers four key aspects of eco-design, applied to electrical engineering. First, it describes current and future methodologies and standards, including regulations, which apply to electrical engineering. In turn, the second chapter is devoted to energy systems and planning, including constraints on the insertion of equipment into the grid. Components such as transformers and cables, their eco-design characteristics and impacts, and their potential to improve the environmental impacts of networks are described in the third chapter. Lastly, the fourth chapter deals with materials in terms of their performance and ecological impact. In the case of electrical equipment, the eco-design approach is also connected to the development of renewable energies and energy efficiency.  .
Part 1  Methodologies and Standards -- 1.1Overview of Eco‐design applications on various types of electronics product development -- 1.2Hazardous substances management in the Supply Chain -- 1.3SWOT analysis of the ISO 14006 application. A practical case and its consequences on eco-designed products -- 1.4Network for building purposes equipment environmental declarations ‐ Towards a Harmonised System -- 1.5Dynamic eco‐design tactic planning for diverse strategies from electric‐electronic industry -- Part 2 Energy System and planning -- 2.1Renewable Energy,an essential element in India's Energy security (electricity).- 2.2Making compatible energy planning with urban decision‐making. Socio‐energetic nodes and geographic configurations -- 2.3Profitable renewable energy hybrid system associated to Battery Energy Storage for the electrification in the Maghreb Region electric: Tunisia Case Study -- 2.4Life Cycle assessment of the energetic flows between a building, its storage and a local production -- 2.5Demand Response Process in Context of the unified LINK-based Architecture.
Keywords: Electric power production; Telecommunication; Electrical Power Engineering; Communications Engineering, Networks; Mechanical Power Engineering